Morphine Enhances HIV Infection of Human Blood Mononuclear Phagocytes through Modulation of β-Chemokines and CCR5 Receptor. (1st November 2002) - Guo, Chang-Jiang; Li, Yuan; Tian, Sha; Wang, Xu; Douglas, Steven D.; Ho, Wen-Zhe
Abstract : Background: Injection drug use remains a significant risk for acquiring HIV infection. The mechanisms by which morphine enhances HIV infection of human immune cells are largely unknown. Objective: In this study, we sought to determine the possible mechanisms by which morphine upregulates HIV infection of human blood monocyte-derived macrophages (MDM). Methods: In this study, MDM were infected with the R5, X4, and R5X4 HIV strains. HIV replication was determined by performing reverse transcriptase activity assays. HIV receptors were determined by performing reverse transcriptase polymerase chain reactions and flow cytometry assays. β-chemokines were analyzed by performing enzyme-linked immunosorbent assays. In addition, HIV R5 strain and murine leukemia virus envelope-pseudotyped HIV infection was performed to determine whether morphine affects HIV infection of macrophages at entry level. Results: Morphine significantly enhanced HIV R5 strain infection of MDM but had little effect on X4 strain infection. The macrophage-tropic R5 strain envelope-pseudotyped HIV infection was markedly increased by morphine, whereas murine leukemia virus envelope-pseudotyped HIV infection was not significantly affected. Furthermore, morphine significantly upregulated CCR5 receptor expression and inhibited the endogenous production of β-chemokines in MDM. The opioid receptor antagonist naltrexone blocked the effects of morphine on the production of β-chemokines. Conclusion: Opiates enhance HIV R5 strain infection of macrophages through the downregulation of β-chemokine production and upregulation of CCR5 receptor expression and may have an important role in HIV immunopathogenesis.